Relationship Of Knowledge, Attitude With SADARI Behavior As An Early Detection Of Breast Cancer In Students Of The Faculty Of Public Health, Teuku Umar University Meulaboh - Arfah Husna; Siti Maisyaroh Fitri Siregar; Azwar Azwar (Universitas Teuku Umar, 2021)
Breast cancer cases are quite high in Indonesia, namely 42 per 100,000 population and are the main cause of death for women in Indonesia. The purpose of this study was to analyze the relationship between knowledge and attitudes with awareness behavior (self-breast examination) in students of the Faculty of Public Health, Teuku Umar University, Meulaboh. The research design was cross sectional with a quantitative approach with univariate and bivariate analysis. The population of this study were female students at the Faculty of Public Health, Teuku Umar University Meulaboh, West Aceh Regency with a sample of 143 female students. The results of the study concluded that most of the respondents had never realized it as many as 84 people (58.7%). The factors of knowledge and attitudes about awareness are related to the behavior of being aware